2006
DOI: 10.1111/j.1365-2036.2006.03128.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide in the treatment of viral gastroenteritis: a randomized double‐blind placebo‐controlled clinical trial

Abstract: SUMMARY BackgroundEnteric viruses including noroviruses and rotavirus are leading causes of diarrhoeal disease and gastroenteritis worldwide, and there is no effective treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
142
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 25 publications
0
142
0
Order By: Relevance
“…Nitazoxanide (NTZ) is a thiazolide antiinfective with activity against a broad range of anaerobic bacteria, protozoa, and viruses (3,6,9,10). While NTZ was originally developed as a treatment for intestinal protozoan infections, its antiviral properties were discovered during the course of its development for treating cryptosporidiosis in patients with AIDS.…”
mentioning
confidence: 99%
“…Nitazoxanide (NTZ) is a thiazolide antiinfective with activity against a broad range of anaerobic bacteria, protozoa, and viruses (3,6,9,10). While NTZ was originally developed as a treatment for intestinal protozoan infections, its antiviral properties were discovered during the course of its development for treating cryptosporidiosis in patients with AIDS.…”
mentioning
confidence: 99%
“…End point studied was the time from first dose of the drug to resolution of symptoms and was significantly low in children who received a 3 day course of nitazoxanide compared to those who received placebo. The same investigator had also done an analogous study in 50 adult patients with similar results [3].…”
Section: Sirmentioning
confidence: 73%
“…Clinical studies on Nitazoxanide (NTZ), a prototype, for the treatment of chronic hepatitis C, have shown that all responders had low levels of serum HCV RNA (7). Thiazolide derivatives have been shown to be effective against many unicellular organisms and viruses (23,24). Thiazolide derivatives were initially developed for the treatment of intestinal infections.…”
Section: Discussionmentioning
confidence: 99%